PENGARUH MODEL PEMBELAJARAN PROJECT BASED LEARNING (PjBL) UNTUK MENINGKATKAN KEMAMPUAN MENULIS KARANGAN NARASI SISWA - Lestari, Asdini Indah; Nainggolan, Fauziah Ahmad Zain; Ritonga, Mara Untung; Adisaputera, Abdurahman (FKIP Universitas Al Washliyah Medan, 2025)
This study aims to describe: (1) the effect of implementing PjBL learning modals on the ability to write narrative essays in grade 5 students of UPT SPF SDN 101783 Saentis in the 2024/2025 Academic Year, (2) categories of narrative essay writing abilities before and after implementing PjBL learning modals in control and experimental classes, and (3) explain the causes of low narrative essay writing abilities in grade 5 students of UPT SPF SDN 101783 Saentis in the 2024/2025 Academic Year. The sample of this study was all grade 5 students of UPT SPF SDN 101783 Saentis in the 2021/2022 Academic Year, totaling 90 students who would be placed in 2 different classes, namely 45 students in the experimental class and 45 students in the control class. The method used in this study was an experiment of the quasi-experimental design type. A narrative essay writing ability test was used to collect data. The research data analysis technique used the t-test formula. The results of the hypothesis test prove that the t count is 6.46 where the t table value is df = 58 which is 1.67, then the t count is obtained.> t table or 6.46> 1.67 so that it can be concluded that H0 is rejected and Ha is accepted. The research findings show that (1) there is an influence of the implementation of PjBL learning capital on the ability to write narrative essays in grade 5 students of UPT SPF SDN 101783 Saentis in the 2024/2025 Academic Year, (2) the category of narrative essay writing ability before and after the implementation of PjBL learning capital is different and shows improvement, (3) based on the results of interviews with students, it is known that the low ability to write narrative essays in grade 5 students of UPT SPF SDN 101783 Saentis in the 2024/2025 Academic Year is that students are less able to write a storyline based on events that occur, students have difficulty expressing